Definitive Chemoradiotherapy for Vulvar Cancer. Issue 9 (November 2016) - Natesan, Divya; Susko, Matthew; Havrilesky, Laura; Chino, Junzo
Abstract : Objectives: This study aimed to evaluate clinical outcomes after chemoradiation (CRT) for the definitive (nonsurgical) treatment of vulvar cancer. Materials and Methods: Women with vulvar cancer treated with definitive CRT at a single academic institution between 1994 and 2015 were retrospectively identified. Overall survival (OS), freedom from local recurrence, freedom from distant recurrence, and late toxicities were estimated using the Kaplan–Meier method at 3 years after radiotherapy completion. Univariate Cox regression models were used to estimate the effects of risk factors on these clinical end points. Acute and late toxicities were assessed according to the Common Terminology Criteria for Adverse Events v. 4.0. Results: Twenty-five women met criteria for inclusion. At 3 years, OS was 71% (95% confidence interval [CI], 49%–93%), freedom from local recurrence was 65% (95% CI, 43%–87%), and freedom from distant recurrence was 78% (95% CI, 59%–97%). Older age was significantly associated with decreased OS (hazard rate, 1.069/y; 95% CI, 1.005–1.124; P = 0.035) and local recurrence (hazard rate, 1.077/y; 95% CI, 1.009–1.150; P = 0.026). Larger size of the primary was borderline associated with distant recurrence ( P = 0.057). Skin changes were the most common late toxicity, with a 3-year rate of late G3 skin toxicity of 45% (95% CI, 20%–69%). The rate of lymphedema at 3 years was 25% (95% CI, 5%–44%). Conclusions: Definitive CRT for advanced vulvar cancer was an effective and well-tolerated approach for women with unresectable disease. Further work is needed to more appropriately select women who will benefit most from a nonsurgical approach. Abstract : Supplemental digital content is available in the text.